Study on Key Technologies of Intelligent IoT Device - Yingqi Wei; Weiping Lin; Ying Li (Dianxin kexue)
Smart IoT devices go into product stage from hype stage.Sensors are being miniaturized，integrated，intelligent and diversified，turn the reality into digital.IoT device’s intelligent is based on power of processor and advanced operation system，and be enhanced by the cloud computing and big data.As smart phone，the smart IoT devices need to build an active ecosystem that engage developers to innovate.The several key technologies development status and future trends were explored，analyzed，and displayed.